RECOMBINANT STRAINS OF SACCHAROMYCES CEREVISIAE FOR ETHANOL PRODUCTION FROM PLANT BIOMASS - A. S. Rozanov; A. V. Kotenko; I. R. Akberdin; S. E. Peltek (Вавиловский журнал генетики и селекции)
Saccharomyces cerevisiae is the most appropriate and the most widely used model organism for industrial production of ethanol from sugars, because yeasts (1) have high rates of growth, fermentation and  biosynthesis of ethanol under anaerobic conditions and (2) are tolerant of high concentrations of ethanol and low pH values. Currently, the most promising source of sugar is lignocellulosic biomass. Sugars derived from it are a mixture of hexoses and pentoses. However, S. cerevisiae strains in current use are poorly adapted to pentasaccharide fermentation. Therefore, it is necessary to optimize the metabolism of currently available bioethanol producers for pentasaccharide consumption. The article presents an overview of existing approaches designed to solve this problem by using recombinant S. cerevisiae strains.